Pengaruh Aplikasi Pengingat Minum Obat (APMO) Terhadap Tingkat Kepatuhan Pasien Diabetes Melitus (DM) di UPTD Puskesmas Simpang Tiga Pekanbaru: The Effect of Medication Reminder Application (APMO) on the Level of Compliance of Diabetes Mellitus (DM) Patients in Community Health Center Simpang Tiga Pekanbaru - Denia Pratiwi; Erni Susanti; Adrian Mulya; Nadya Putri Auliya Serawaidi (LPPM Universitas Abdurrab, 2025)
Diabetes Melitus therapy can uses more than one type of drug preparation over a long period of time and has the potential to reduce the level of patient compliance in undergoing therapy. Non-compliance with planned therapy will cause therapy failure which can cause complications in DM patients. Some interventions that can be used to help improve compliance in DM patients include the Medication Reminder Application (APMO) via smartphone with two different applications. The purpose of this study was to determine the effect of the Medication Reminder Application (APMO) on the level of compliance of Diabetes Mellitus (DM) patients in the Community Health Center Simpang Tiga Pekanbaru. This study used a non-experimental method with a cross-sectional approach. The total population was 1358 patients and a sample of 93 patients who met the inclusion criteria. The sample of 93 people was divided into three groups, namely group APMO A of 31 people, group APMO B of 31 people and a group not given APMO of 31 people. The results of this study indicate that the Kruskal-Wallis analysis p-value = <0.001 (α <0.05) so that there are differences in the 3 groups, while the Chi-Square analysis p-value = <0.001 (α <0.05), thus indicating that the provision of APMO has a significant effect on the level of compliance of DM patients at the UPTD Puskesmas Simpang Tiga Pekanbaru.